Media and politics in the muslim world:unfriendly relationship between press freedom and Illiberal government - Moniruzzaman, Md. (Medwell Publishers, 2018)
The research assesses media freedom or media sustainability and politics in 37 Muslim majority countries. Media sustainability is measured using the International Researches and Exchange Board (IREX) score whereas political regime is measured using the Economist Intelligence Unit’s Index of Democracy. The analysis indicates that three countries fall in the unsustainable media category; about 20 countries fall in the “unsustainable mixed system” of media. However, another set of eight countries are characterized as “near sustainability” category. None of the countries studied has an average score to enable it to be in the “sustainable” category.